Environmental Efficiency and Random Convergence Analysis of Large-scale Pig Breeding in China *. (June 2020) - Zhang, Ruixin; Fu, Xinhong; Li, Jianqiang
Abstract: As the scale of live pigs in China continues to accelerate, the agricultural non-point source pollution caused by it is becoming increasingly serious. In this paper, the SBM-Undesirable model was used to measure the environmental efficiency of pig breeding in different scales in year 2008-2017, and the efficiency was analyzed by random convergence. Results show: from the overall average, the environmental efficiency of pig breeding in China is medium-scale, large-scale and small-scale in order, and the three-scale pig breeding has random convergence characteristics. From the perspective of different regions, with the environmental efficiency as a judge, the three scales of potential development zones perform well, and only the small-scale pig breeding shows random convergence; large-scale mode in key development zones performs well with no signs of random convergence, has poor stability, while the other two remain stable at a low level; small and medium-scale modes perform better in moderate development zones, all showing no features of random convergence; the three scales in constrained development zones don't perform well, and all remain stable at a lower level. Based on the above results, this paper put forward differentiated policies for different scales and regions to promote healthy and green development of pig scale breeding.